Plain Language Summary Required for Submission to Journal of Geophysical Research: Solid Earth. Issue 5 (19th May 2021) - Manighetti, Isabelle; Abercrombie, Rachel E.; Ben‐Zion, Yehuda; Bernabé, Yves; Bostock, Michael; Dekkers, Mark J.; Parman, Stephen W.; Schmitt, Doug; Tregoning, Paul
Abstract: The editors of JGR: Solid Earth announce that Plain Language Summaries will be required for all manuscripts. Plain Language Summary: All manuscripts published in JGR‐Solid Earth will include a Plain Language Summary. Key Point: An announcement that Plain Language Summaries will be required for all articles published in the journal